Male reproductive system of the freshwater prawn Macrobrachium brasiliense (Decapoda: Palaemonidae): Notes on spermatophore formation and sperm count - Nogueira, Caio S. [UNESP]; Antunes, Mariana [UNESP]; Zara, Fernando J. [UNESP]; Costa, Rogerio C. [UNESP] (Elsevier, 2023)
Studies on the morphology of the reproductive system are essential for understanding the reproduction processes of species or even within genera or families. The present study aimed to describe the functional morphology of the male reproductive system, spermatophore formation, and sperm count of Macrobrachium brasiliense. The anatomy of the reproductive system consists of a pair of testes from which the vasa deferentia (VD) starts, extending to the fifth pair of pereopods. The VD is divided into three regions: proximal (PVD), middle (MVD), and distal (DVD). In the PVD, there is a prominent fold, the typhlosole, formed by columnar cells. The typhlosole disappears in the MVD, being incorporated into one of the faces of the VD wall, identified by its simple columnar epithelium while the remainder of the vessel wall is formed by squamous or simple cubic epithelium. Columnar cells produce type-II and III secretion. The epithelium in the DVD is made up only of cubic cells. Low sperm concentration was observed when compared to other species of the genus Macrobrachium. In conclusion, the typhlosole and columnar epithelium are responsible for the asymmetric spermatophore, which seems the pattern of Macrobrachium that is probably shared with other caridean shrimps.
Keywords: Caridea; Histochemistry; Histology; Testes; Typhlosole